Knowledge-management collaboration and labor brokerage performance - Downing, James A. (Economic and business review, 2026)
Entrepreneurs operating in knowledge-intensive markets will seek to reduce costs with tacit-knowledge-management mechanisms. When seeking a competitive advantage in knowledge-intensive industries, individuals will create value from general market information and engineer the transaction cost for clients. These market-making individuals will operate within a firm to gain benefits from information-sharing collaboration. Firms will make investments in tacit- information sharing to assist individual collaboration, resulting in increased firm performance. The value creation process for knowledge-intensive markets is crafted from general market information. The value appropriation process is unique to knowledge-intensive industries with the engineering of a client’s transaction costs as a competitive ad- vantage. The research develops a schema for the engineering of transaction costs using entrepreneurial market-making efficiencies mapped to the determinants of transaction costs theory. The multilevel econometric model examines both firm-level and individual-level investments in tacit-knowledge management. Results suggest firm-level investments in information sharing may not improve the performance of the individuals in the firm. However, when there is a firm structure and individuals actively share information, then efficiency is created, leading to larger deals and increased firm performance. Future research developing those efficiencies found in knowledge-management strategies is needed. This article also calls for further development and observations of engineering transaction costs, specifically in knowledge- intensive industries.
Keywords: business efficiency; delovna uspešnost; entrepreneurship; knowledge management; labour efficiency; obvladovanje znanja; podjetništvo